Creative Inculturation and the Unity of Faith: Working papers on Living Faith and Cultures Vlll - Pottampuzha, P (Journal of Dharma, 1989)
Arij A. Roest Crollius, et. al, Creative /ncu/turation and the Unity of Faith, Working papers on Living Faith and Cultures Vlll, Rome: Pontifical Gregorian University, 1986. pp. xii+76.